2017
DOI: 10.1017/s1742170516000478
|View full text |Cite
|
Sign up to set email alerts
|

Hydroponic production of vegetable Amaranth (Amaranthus cruentus) for improving nutritional security and economic viability in Kenya

Abstract: This study used a multidisciplinary approach to evaluate the potential for hydroponic production of vegetable amaranth (Amaranthus cruentus) in Kenya. Hydroponic systems have potential for increased efficiency in water and land use, but their potential has not been critically evaluated in many developing countries. To address this gap in knowledge, this study assessed the nutritional density and economic viability of hydroponic systems built from local materials. Specifically, vegetable amaranth was grown hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, it differed from that of Pereira (2019), which observed average leaf P content of 3.8 g kg -1 for the variety Viçosa. The difference between P content on leaf tissues may be a result of different fertilizer properties, which directly influence nutrient accumulation in plants (Croft et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, it differed from that of Pereira (2019), which observed average leaf P content of 3.8 g kg -1 for the variety Viçosa. The difference between P content on leaf tissues may be a result of different fertilizer properties, which directly influence nutrient accumulation in plants (Croft et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Looking at this aspect for the hydroponic unit, it can be concluded that the technical feasibility of the unit at scale has not been proven [11]. Small-scale and low-cost hydroponic units are gaining more attention as a way to alleviate poverty and improve farmers' resilience [106,107,108].…”
Section: Challenges and Limitations Of The Design Approachmentioning
confidence: 99%
“…Hydroponic fruit production has extensively expanded globally in recent decades, due to the ease of nutrient management and increased efficiency of water and fertiliser use. Additionally, manipulating the nutrient levels in hydroponic solutions were effective in controlling the plant growth, yield, and fruit quality [1][2][3][4][5]. In recent years, with the rapid development of precision agriculture, crop cultivation in the closed hydroponic systems has become the best choice for well-maintaining stable cultivation conditions through fertiliser management and nutrient monitoring.…”
Section: Introductionmentioning
confidence: 99%